ANALISIS EKO-EFISIENSI PADA UKM TEPUNG TAPIOKA (Studi Kasus Pada UD Sinar Cerah Kecamatan Margoyoso Kabupaten Pati) - Devi Widyana Wulan; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2020)
Eco-efficiency is a concept/strategy the delivery of competitive price of goods and services that satisfy human needs and bring the quality of life, while progressively reducing ecological impacts and resource intensity throughout the life-cycle, to a level at least in line with the earth’s estimated carrying capacity. Eco-efficiency actions include reduction of the material intensity of goods and services, reduction of the energy intensity of goods and services, reduction of toxic dispersion, enhancement of materials recyclability, maximum sustainable, use of renewable resources, extension of product durability, and maximum service intensity of products. The problem that occurs at Tapioca Flour SMEs UD Sinar Cerah is a huge NPO cost which is 78.5% of the total production cost. This study aims to determine the application of eco-efficiency in the Tapioca Flour SMEs UD Sinar Cerah, Margoyoso District, Pati Regency. This research uses a descriptive-analytical method with a qualitative approach. Data collection techniques used include observation, oral interviews ,and literature study. Observations were made on the use of raw materials, water, and energy used in production. The analysis showed that in one year UD Sinar Cerah produced 3,354,780 kg of tapioca flour. The accumulated annual cost of NPO UD Sinar Cerah is Rp. 17,282,564,465.00. UD Sinar Cerah has the opportunity to implement eco-efficiency measures in the process of cutting poles, settling, and encircling to save NPO costs as much as 164,037,436.00 per year. The suggestion given to Tapioca Flour SMEs UD Sinar Cerah is to increase the accuracy and caution in the use of raw materials, energy, and water that has not been measured.